Peranan Dinas Pariwisata Dalam Meningkatkan Kualitas Atribut Destinasi Wisata Goa Kelelawar Yang Dapat Menciptakan Loyalitas Wisatawan Dikota Padang - Susan Khairiyah (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2024)
Tourism is a key sector that is expected to drive the Indonesian economy. Good management brings certain impacts and benefits to the area. One area in Indonesia that has great tourism potential is the city of Padang. Tourism includes various types of tourism such as nature tourism, family tourism, historical tourism, religious tourism, seaside tourism, fishing tourism and village tourism. Therefore, its implementation requires good leadership and development over time. This is because tourism creates an attraction for tourists when visiting and creates loyalty among tourists. Tourism has a positive impact so it needs to be developed further. The community and government are working together to continue to increase tourism in the area